METHODS OF USING MODERN TECHNOLOGIES OF TEACHING IN PRIMARY SCHOOLS - Boltaboyev Azizbek Hasanboy o’g’li; Alijonova Maftunahon Botirjon qizi (Galaxy International Interdisciplinary Research Journal, 2021)
Based on educational goals, students improve their communication culture by developing independent thinking, oral and written literacy, logical thinking. On the basis of the educational purpose the spiritual, ideological, delicate education is given. In the process of language learning, there is an opportunity to get closer to the cultural and moral values of the people. Based on the above, based on our experiences, we express our views on ways to teach through the use of interactive methods in the classroom.